Effects of citric acid and acetic acids on the stability and acceptability of purple sweet potato (Ipomoea batatas) ketchup. - Martirez, Tanya Kristine Cerbo
Tomato ketchup is among the popular condiment as it is used as flavoring ingredient in many foods. The high perishability of tomatoes contribute to a high cost of production and more expensive products. Purple sweet potato (PSP) as a more cheaper, stable and nutritious alternative to tomato in the production of ketchup. Two formulations of Purple Sweet Potato ketchup that differed in the type of acidulants, namely acetic acid (FAc) and citric acid (FC) were assessed for the stability of the ketchup as it was stored in chilled condition (4-7°C) for 12 days. The pH of both formulations of ketchup had decreasing trends during storage with FAc ranging 4.10 to 4.02, and FC ranging 4.12 to 3.98. Anthocyanin content during storage decreased, with FAc from 22.71 mg/L to 20.62 mg/L, and FC from 22.43 mg/L to 18.76 mg/L. The radical scavenging activity for in both formulations decreased during storage with FAc from 75.28% to 70.05% and FC from 75.15% to 70.07%. The yeast and mold count for both formulations during storage was within the safety standard of ketchup, <104 CFU/g. The color of both formulations changed from dark magenta to light magenta during the storage period. Between the two formulations, the PSP ketchup treated with citric acid was the most preferred, with a rating of ?like moderately?, while the PSP ketchup treated with acetic acid was rated ?like slightly?. The calculated cost for a 600-ml bottle of PSP ketchup treated with citric acid was the most preferred, with a rating of ?like moderately?, while the PSP ketchup treated with acetic acid was rated ?like slightly?. The calculated cost for a 600-ml bottle of PSP ketchup treated with citric acid was Php 27.67. PSP ketchup treated with vinegar was at Php 29.24. Compared to other commercial brands of ketchup, both formulations of PSP ketchup are considerably cheaper.